New Advances in Information Systems and Technologies - Rocha, Álvaro; Correia, Ana Maria; Adeli, Hojjat; Reis, Luis Paulo; Mendonça Teixeira, Marcelo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book contains a selection of articles from The 2016 World Conference on Information Systems and Technologies (WorldCIST'16), held between the 22nd and 24th of March at Recife, Pernambuco, Brazil. WorldCIST is a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges of modern Information Systems and Technologies research, together with their technological development and applications. The main topics covered are: Information and Knowledge Management; Organizational Models and Information Systems; Software and Systems Modeling; Software Systems, Architectures, Applications and Tools; Multimedia Systems and Applications; Computer Networks, Mobility and Pervasive Systems; Intelligent and Decision Support Systems; Big Data Analytics and Applications; Human-Computer Interaction;Health Informatics; Information Technologies in Education; Information Technologies in Radiocommunications.
Information and Knowledge Management -- Organizational Models and Information Systems -- Software and Systems Modeling -- Software Systems, Architectures, Applications and Tools -- Multimedia Systems and Applications -- Computer Networks, Mobility and Pervasive Systems -- Intelligent and Decision Support Systems -- Big Data Analytics and Applications -- Human-Computer Interaction -- Health Informatics.-Information Technologies in Education.-Information Technologies in Radiocommunications.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence